Emotional Language in Alcipron’s Letters: Closing a Letter with a Threat - Thoma, Marianna (Classica et Mediaevalia, 2024)
Alciphron’s books of imaginary letters depict both the rural and urban environment of Attica in the 4th century BC, in miniature and from the perspective of lowerclass characters. Alciphron uses all the rhetorical options offered by the epistolary form to illustrate the thoughts, feelings and experiences of his characters. The aim of this paper is to discuss the use of threats, and their function as rhetorical devices and/or means of expressing emotions in Alciphron’s letters. I will demonstrate that the author may not only have been inspired by New Comedy and other literary genres, but also by his contemporary private correspondence in which various threats towards the addressee are used as a rhetorical strategy, as shown by the preserved papyri and ostraca from Egypt.